Go With Your Gut: Understanding Probiotics - Wendy J. Dahl; Volker Mai (EDIS)
Probiotics are known as “good bacteria.” Often, when we think of bacteria, we think about the ones that cause sickness, and while there are many bacteria that can cause disease, there are many more that are beneficial to our health. Probiotics are live microorganisms that, when administered in adequate amounts, provide a health benefit. Learn more in this 3-page fact sheet written by Wendy J. Dahl and Volker Mai and published by the UF Department of Food Science and Human Nutrition, June 2011.